2008
DOI: 10.1007/978-0-387-78748-0_6
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Nicotine in Smoking: A Dual-Reinforcement Model

Abstract: Models of intravenous nicotine self-administration in laboratory animals are being used to investigate the behavioral and neurobiological consequences of nicotine reinforcement, and to aid in the development of novel pharmacotherapies for smoking cessation. Central to these models is the principle of primary reinforcement, which posits that response-contingent presentation of a primary reinforcer, nicotine, engenders robust operant behavior, whereas response-independent drug delivery does not. This dictum of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
227
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(242 citation statements)
references
References 60 publications
(98 reference statements)
13
227
0
Order By: Relevance
“…Finally, all previous self-administration research in this area has focused on the impact of MAO inhibition on the primary reinforcing effect of nicotine. However, we have previously shown that rats will respond for a visual stimulus (VS) consisting of a 1-s cue light presentation and a 1-min white houselight offset, and that responding for the VS is increased in rats receiving non-contingent infusions of nicotine (Caggiula et al, 2009;Donny et al, 2003;Palmatier et al, 2006;Rupprecht et al, 2015). The action of nicotine to increase the value of other reinforcers is known as reinforcement enhancement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, all previous self-administration research in this area has focused on the impact of MAO inhibition on the primary reinforcing effect of nicotine. However, we have previously shown that rats will respond for a visual stimulus (VS) consisting of a 1-s cue light presentation and a 1-min white houselight offset, and that responding for the VS is increased in rats receiving non-contingent infusions of nicotine (Caggiula et al, 2009;Donny et al, 2003;Palmatier et al, 2006;Rupprecht et al, 2015). The action of nicotine to increase the value of other reinforcers is known as reinforcement enhancement.…”
Section: Introductionmentioning
confidence: 99%
“…The action of nicotine to increase the value of other reinforcers is known as reinforcement enhancement. The reinforcement enhancement effect has been shown to be as important or more important than the primary reinforcing effect of nicotine for nicotine self-administration (Caggiula et al, 2009). The impact of MAO inhibition on the reinforcement enhancing effect of nicotine is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Here we propose that IV nicotine self-administration may be particularly amenable to devaluation through techniques typically employed with natural rewards (ie, pairing nicotine with lithium-induced nausea) due to the unique characteristics of nicotine self-administration. First, rats are relatively poor at titrating nicotine intake with changing infusion dose, but are highly sensitive to non-pharmacological factors, including physical response requirements (nose poke vs lever press; Clemens et al, 2010) and the presence of nicotine-related cues (Caggiula et al, 2009). Second, nicotine produces strong interoceptive cues that can enter into associations with other stimuli (Charntikov et al, 2012), such as lithium-induced nausea (Pittenger and Bevins, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nicotine dramatically increases responding for other reinforcers even when nicotine delivery is not contingent on the animal ' s behavior ( Donny et al, 2003 ) or when nicotine is concurrently available through another operant ( Palmatier et al, 2006 ). These outcomes have led to the dual reinforcement model, which recognizes two actions of nicotine: ( a ) it is a primary reinforcer and ( b ) it enhances the reinforcing effects of concurrently available stimuli ( Caggiula et al, 2009 ). These effects are consistent with data from studies measuring intracranial self-stimulation that show nicotine increases sensitivity of the neural pathways mediating reward ( Bauco & Wise, 1994 ;Huston-Lyons & Kornetsky, 1992 ;Kenny & Markou, 2006 ).…”
Section: Introductionmentioning
confidence: 99%